Application of organic matter and biofertilizer to improve growth and yield of maize on soil damaged by volcanic ash of Mount Kelud in East Java - S Hardianita; R M Bosas; Y Nuraini (Journal of Degraded and Mining Lands Management, 2015)
Volcanic ash from the eruption of Mount Kelud in 2014 damaged some agricultural areas grown with maize in Malang of East Java. The purpose of this study was to elucidate the effect of organic fertilizers and biological fertilizers on growth and yield of maize on soils damaged by volcanic ash from the eruption of Mount Kelud. A pot experiment was conducted in the glasshouse of Balitkabi, Kendalpayak, Malang from July 2014 to February 2015. The treatments tested in this study were combinations of three mixtures of soil and volcanic ash (90%:10%, 80%:20%, and 70%:30%), and two doses of biofertilizer (25 and 35 kg / ha). Each treatment was added with 5 t organic matter/ha. A total of 10 kg of each mixture of soil and volcanic ash was placed in a 15 kg plastic pot. Each treatment received 100 kg inorganic fertilizer / kg containing 15% N, 15% P, and 15% K. Three seeds of maize (NK33 variety) were planted in each pot and thin to one plant after one week. The experiment was conducted for 14 weeks. The results showed that application of organic matter and biofertilizer did not significantly improve fertility of soil mixed with volcanic ash from the eruption of Mount Kelud. Yield of maize was not significantly improved by the application of organic matter and biofertilizer on soil mixed with volcanic ash. The contents of carbohydrates and proteins in maize seeds were also not affected by application of organic matter and biofertilizer.